Pelatihan Internet of Things (IoT) Berbasis Arduino sebagai Upaya Peningkatan Literasi Teknologi - Kadek Surya Adi Saputra; Ayu Chrisniyanti (Pusat Riset dan Inovasi Nasional, 2025)
Arduino-based Internet of Things (IoT) training is a strategic effort to enhance students’ technological literacy in the digital era. Limited practical understanding of IoT concepts and applications remains a major challenge in technology education. This community service activity aims to improve students’ technological literacy through hands-on IoT training using Arduino that integrates theoretical knowledge with practical implementation. The activity was conducted in three stages: preparation, implementation, and evaluation. A total of 20 students from ITB STIKOM Bali participated in face-to-face training sessions. The evaluation was carried out using pre-test and post-test instruments to measure participants’ understanding of IoT concepts and Arduino applications. The results indicate a significant improvement, where the average pre-test score of 45.5 increased to 81.5 in the post-test, representing a learning improvement of 79.12%. In addition to cognitive improvement, participants demonstrated increased confidence and practical skills in designing and implementing simple IoT systems. These findings confirm that Arduino-based IoT training is effective in enhancing students’ technological literacy. This activity is expected to serve as an applicative learning model that can be sustainably implemented to support students’ readiness in facing rapid technological developments and workforce demands